Recurrent Brain Abscess in 40-Years-Old Female Associated with Ventricular Septal Defect: A Case Report - Azmi Farah Fairuzya; Martha Oktavia Dewi Savitri; Hanindia Riani Prabaningtyas; Yasuhiro Watanabe; Takenobu Murakami; Yuki Tajiri (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2025)
Background: Ventricular septal defect (VSD) is one of the critical risk factors for brain abscess. The unsterile blood in uncontrolled cyanotic congenital heart disease cases will travel to the brain after escaping the filtration mechanism and cause brain abscess. Case: A 40-year-old female presented with a two-week course of moderate headaches, worsening severely four days before admission. Neurological manifestations included attention deficits, dysarthria, right-sided hemiparesis, and proper facial palsy. Laboratory findings indicated leukocytosis and polycythemia. Echocardiography revealed VSD. Brain MRI with contrast suggested a single abscess lesion in the left occipital lobe. A histopathological examination confirmed the diagnosis. Antibiotics were administered during hospitalization, with outpatient treatment afterward. A one-month follow-up revealed new symptoms and a subsequent surgical excision. Discussion: Brain abscess remains a challenging and life-threatening case despite advanced diagnostic techniques. Uncontrolled cyanotic heart disease might be an essential risk factor for brain abscess occurrence. Thorough diagnostic examinations must be conducted to establish the diagnosis. The optimal empirical-targeted antibiotic treatment is a cornerstone of management. After antibiotic therapy, a surgical approach must be considered in lesions with large-size or nonoptimal size reduction. It is essential to comprehensively manage brain abscesses and their etiology to reduce the recurrence rate. Conclusion: Brain abscess associated with uncontrolled cyanotic congenital heart disease requires comprehensive treatment involving antibiotics and surgery. Addressing underlying causes and cost-effective follow-ups with clinical and monthly imaging assessments are essential.